2017
DOI: 10.1080/00343404.2016.1265104
|View full text |Cite
|
Sign up to set email alerts
|

Causal relations between knowledge-intensive business services and regional employment growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 61 publications
1
23
0
3
Order By: Relevance
“…6 As employment in the tech sector expands and as these employees earn more, their demand for many types of local services, from coffee shops to orchestras, increases. Consistent with this expectation, several studies have found positive associations between employment in the tradable sector and employment in the non-tradable sector (Moretti and Thulin, 2013;van Dijk, 2017;Brenner et al, 2018).…”
Section: Tradable Vs Non-tradable Industriesmentioning
confidence: 83%
“…6 As employment in the tech sector expands and as these employees earn more, their demand for many types of local services, from coffee shops to orchestras, increases. Consistent with this expectation, several studies have found positive associations between employment in the tradable sector and employment in the non-tradable sector (Moretti and Thulin, 2013;van Dijk, 2017;Brenner et al, 2018).…”
Section: Tradable Vs Non-tradable Industriesmentioning
confidence: 83%
“…Many studies focus on spatial variation of innovation in the knowledge-intensive business sector. The subject of their analysis is the regional diversification of companies in the KIS sector (Brenner et al, 2018;Dolores & Shearmur, 2012;Klaesson & Norman, 2015;Pauceanu, 2015;Ženka et al, 2017). The mentioned articles analyse the KIS in some countries (Sweden, Germany, the Czech Republic).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first group contains works that link regional innovation efficiency and KIBS (i.e. Brenner et al, 2018;Gallego & Maroto, 2015). The second group of authors and we focus on the location of KIS (Pauceanu, 2015;Ženka et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we briefly review this methodology. For interesting applications of this method, see Brenner et al (2017); Guerini and Moneta (2017); Ciarli, Coad, and Moneta (2018);and Herwartz (2018).…”
Section: Svar Analysismentioning
confidence: 99%